Phonon-mediated high-T c superconductivity in hole-doped diamond-like crystalline hydrocarbon - Chao-Sheng Lian (Nature Portfolio, 2017)
Abstract We here predict by ab initio calculations phonon-mediated high-T c superconductivity in hole-doped diamond-like cubic crystalline hydrocarbon K 4-CH (space group I21/3). This material possesses three key properties: (i) an all-sp 3 covalent carbon framework that produces high-frequency phonon modes, (ii) a steep-rising electronic density of states near the top of the valence band, and (iii) a Fermi level that lies in the σ-band, allowing for a strong coupling with the C-C bond-stretching modes. The simultaneous presence of these properties generates remarkably high superconducting transition temperatures above 80 K at an experimentally accessible hole doping level of only a few percent. These results identify a new extraordinary electron-phonon superconductor and pave the way for further exploration of this novel superconducting covalent metal.